Konstruksi Wacana dalam Iklan Ajinomoto Health Provider: Analisis Wacana Kritis Norman Fairclough: Discourse Construction in Ajinomoto Health Provider Advertisements: Norman Fairclough’s Critical Discourse Analysis - Putri, Nia Novita; Hidayah, Isnaini Rahmah; Zakaria, Masduki (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study analyzes discourse construction in Ajinomoto's Health Provider advertising campaign using Norman Fairclough's Critical Discourse Analysis approach. The study employs a descriptive qualitative method with Fairclough's three-dimensional analysis framework, namely the textual dimension, discursive practice, and social practice. Data were drawn from three advertisements titled Bijak Garam Freeze, Langkah Kecil Berarti: Plastic Reduction and Recycle, and The Role Model, published through Youtube platforms. The findings reveal that at the textual dimension, the advertisements employ four main language strategies, namely statistical data usage, invitational diction, practical solution presentation, and corporate identity formation, reinforced by visual representations of community harmony. At the discursive practice dimension, the three advertisements integrate medical health discourse and ecological discourse through production strategies that position company employees as peer-to-peer communication intermediaries. At the social practice dimension, the campaign exploits the social context of hypertension and global pressure on plastic reduction to construct the company's discursive authority. The most significant finding lies in the appointment of Ajinomoto employees as Health Provider representatives, which blurs the boundary between public health education and marketing communication strategy. This study contributes to the development of critical discourse analysis in the context of food product advertising in Indonesia.